Optimal Return Analysis Using the Geometric Mean Method from Daily Data of Technology Sector Stocks: Analisis Return Optimal Menggunakan Metode Geometric Mean Dari Data Harian Saham Sektor Teknologi - Siti Marenda Siregar; Marieska Lupikawaty; Agung Anggoro Seto (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to examine the differences in stock returns and identify the most optimal return within the technology sector companies listed in the LQ45 index. The analysis employs two technical indicators, namely the Relative Strength Index (RSI) and the Stochastic Oscillator (SO). The research uses a quantitative approach with a descriptive method. The data consist of daily stock closing prices from April 2024 to March 2025. The sample includes four companies: PT Telkom Indonesia Tbk, PT XL Axiata Tbk, PT Indosat Tbk, and PT Gojek Tokopedia Tbk. Data analysis was conducted through descriptive statistics, normality testing, homogeneity testing, and hypothesis testing using the Kruskal-Wallis method. The results indicate that there is no significant difference in stock returns between the two technical indicators, with a significance value of 0.518, which exceeds the 0.05 threshold—thus, the null hypothesis is accepted. Additionally, based on the Geometric mean calculation, PT Gojek Tokopedia Tbk recorded the highest return on both RSI and SO indicators. These findings suggest that RSI and SO can be used interchangeably in stock return analysis, and PT Gojek Tokopedia Tbk is recommended as the top investment option in the technology sector based on return potential.